INFORMATION DEVIAS ON THE BASIK OF UNIFUNCTION TRANSISTOR STRUCTURE - Lishchynska, Ludmyla; Baraban, Marija (Scientific Works of Vinnytsia National Technical University, 2015)
On the base of reactive properties of unijunction transistor, there had been developed the elements of information devices, which, in comparison with the known analogues, have the improved technical characteristics, namely: improved reliability, good quality, lower level of noise, small dimensions.